Breast Abscess Mimicking Breast Carcinoma in Male - Debasis Gochhait; Priyadarshini Dehuri; Sandyya Umamahesweran; Rohan Kamat (Wolters Kluwer Medknow Publications, 2018)
Male breast can show almost all pathological entities described in female breast. Inflammatory conditions of the breast in male are not common; however, occasionally, it can be encountered in the form of an abscess. Clinically, gynecomastia always presents as a symmetric unilateral or bilateral lump in the retroareolar region, and any irregular asymmetric lump raises a possibility of malignancy. Radiology should be used as a part of the triple assessment protocol for breast lump along with fine-needle aspiration cytology for definite diagnosis and proper management.